Examination of exhaustive cloning attempts reveals that C. elegans piRNAs, transposons, and repeat sequences are efficiently cloned in yeast, but not in bacteria - Sagy, Or; Shamir, Ron; Rechavi, Oded (Frontiers in Genetics, 2014)
Genome sequencing requires insertion of random fragments of the sequenced organism’s DNA into a unicellular host, most often Escherichia coli bacteria. This manipulation was found in the past to be analogous to naturally occurring horizontal gene transfer, and moreover has proved valuable to understanding toxicity of foreign genetic elements to E. coli. Sequencing of the Caenorhabditis elegans genome was similarly achieved via DNA transformation into E. coli. However, numerous attempts have proven a significant percentage of the genome unclonable using bacteria, although clonable via yeast. We examined the genomic segments that were not clonable in bacteria but were clonable in yeast, and observed that, in line with previous hypotheses, such sequences are more repetitive on average compared with the entire C. elegans genome. In addition, we found that these gap-sequences encode significantly more for DNA transposons. Surprisingly, we discovered that although the vast majority of the C. elegans genome is clonable in bacteria (77.5%), almost all the thousands of sequences that encode for PIWI-interacting small RNAs, or 21U-RNAs (91.6%) were only clonable in yeast. These results might help understanding why most piRNAs in C. elegans are physically clustered on particular loci on chromosome IV. In worms and in a large number of other organisms, piRNAs serve to distinguish “Self” from “Non-Self” sequences, and thus to protect the integrity of the genome against foreign genetic elements, such as transposons. We discuss the possible implications of these discoveries.